(3GHb bhjG (B:s 365 (3jheG aj GdSfI (B/s - (3dhaGJh, Ojejs 1992-; (3ecJHI LQjQ (B((3GdQjGV(B)s ([(3GdQjGV(B] :s (3ecJHI LQjQ,s, 2019)
(3gPG GdcJGH gh eRjL Hjf GdJfejI hGdSjQI GdPGJjI hgh YHGQI Yf ePcQGJ JcJH HTcd eSJeQ deOI SfI Cj (B365 (3jhe hJMJhj ePcQGJ Ojej Ydi GbJHGSGJ ef cJH hcdeGJ NGUI hfUGFM hGbJQGMGJ hJCedGJ hCgOGa jhejI hNhGWQ hGdcGJHI JTGQc GdeYLHjf eTGYQgG heTGcdgG GdTNUjI CedG efgG aj eSGYOJge hefMge GdbhI hGdGdgGe hWHYG fLMJ aj gPg GdegeI HTcd cHjQ(B.s
(3HHdjhLQGajI (B: (3UaMI (B403.s
Keywords: (3GdfLGM GdTNUjs; (3GdJbOe GdTNUjs